2020
DOI: 10.1109/tie.2019.2926056
|View full text |Cite
|
Sign up to set email alerts
|

Regionless Explicit Model Predictive Control of Active Suspension Systems With Preview

Abstract: Latest advances in road profile sensors make the implementation of pre-emptive suspension control a viable option for production vehicles. From the control side, model predictive control (MPC) in combination with preview is a powerful solution for this application. However, the significant computational load associated with conventional implicit model predictive controllers (i-MPCs) is one of the limiting factors to the widespread industrial adoption of MPC. As an alternative, this paper proposes an explicit m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…Model predictive control was chosen as the actuator-control method because it not only considers actuator limitations in the process of vehicle optimization, but can also effectively apply terrain information to improve control effect. Several model predictive controllers for vehicle active suspension systems have been proposed [21,28], but they did not give a detailed description of estimating elevation map. In this paper, we proposed the method for road profile estimation and model predictive control based on reference [27].…”
Section: Model Predictive Control With Previewmentioning
confidence: 99%
See 1 more Smart Citation
“…Model predictive control was chosen as the actuator-control method because it not only considers actuator limitations in the process of vehicle optimization, but can also effectively apply terrain information to improve control effect. Several model predictive controllers for vehicle active suspension systems have been proposed [21,28], but they did not give a detailed description of estimating elevation map. In this paper, we proposed the method for road profile estimation and model predictive control based on reference [27].…”
Section: Model Predictive Control With Previewmentioning
confidence: 99%
“…Result showed that the terrain profile information could be well estimated, and ride comfort and handling stability were also improved with the proposed method. Theunissen et al [28] proposed an explicit model predictive control method that used the road information obtained by LiDAR as the signal input to control the active suspension system. Experiment results showed that the heave and pitch acceleration of the sprung mass was reduced compared with the passive suspension system and skyhook controllers.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the good effect of lateral lane change for ACVs, the dynamic planned trajectory must be accurately tracked using low control consumption and maintaining stable vehicle states. In [24, 25], the reference trajectory is fed to the controller through the multipoint preview operation. The control strategy is then designed by combining trajectory feed‐forward with states feedback to obtain good effects of the reference trajectory tracking.…”
Section: Dllc Control Strategymentioning
confidence: 99%
“…As shown in Fig. 6, the references of longitudinal and lateral displacements can be obtained by the multi‐preview [24, 25, 34].…”
Section: Dllc Control Strategymentioning
confidence: 99%
See 1 more Smart Citation